2009
DOI: 10.3347/kjp.2009.47.2.93
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Diagnosis: A Brief Review

Abstract: Malaria is a major cause of death in tropical and sub-tropical countries, killing each year over 1 million people globally; 90% of fatalities occur in African children. Although effective ways to manage malaria now exist, the number of malaria cases is still increasing, due to several factors. In this emergency situation, prompt and effective diagnostic methods are essential for the management and control of malaria. Traditional methods for diagnosing malaria remain problematic; therefore, new technologies hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
402
1
20

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 446 publications
(457 citation statements)
references
References 78 publications
4
402
1
20
Order By: Relevance
“…This study showed no statistically significant species variation in causing leucopenia (P value>0.05). Leucopenia is observed in 10% cases of P.falciparum and 19.51% of P.vivax infection, which is comparable with study of F.Ellis McKenzie et al ,which showed 10.7% cases of P. falciparum and 15.2% cases of P.vivax infections 20 . In comparative study of Ranjini CY et al 12 Leukopenia and neutropenia primarily reflects the state of hypersplenism.…”
Section: Discussionsupporting
confidence: 79%
“…This study showed no statistically significant species variation in causing leucopenia (P value>0.05). Leucopenia is observed in 10% cases of P.falciparum and 19.51% of P.vivax infection, which is comparable with study of F.Ellis McKenzie et al ,which showed 10.7% cases of P. falciparum and 15.2% cases of P.vivax infections 20 . In comparative study of Ranjini CY et al 12 Leukopenia and neutropenia primarily reflects the state of hypersplenism.…”
Section: Discussionsupporting
confidence: 79%
“…The major means to effective disease management is quick and accurate diagnosis, it is one of the main interventions of the Global Malaria Control Strategy [16,1]. However, malaria infection cannot be diagnosed with symptoms only, it should be confirmed by laboratory diagnosis [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Plasmodium falciparum has been incriminated to cause the most serious and sometimes fatal type of malaria most especially in Africa. The other human malaria species, P. vivax, P. ovale, P. malariae, and sometimes P. knowlesi which cause acute, severe illness but mortality rates are low [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Although few cases of post liver transplantation malaria have been reported in the literature [7], this is the first case of Plasmodium falciparum malaria in an ABOi-LDLT. Possible routes of malarial infection were Reactivation malaria, transmission through transplanted liver and transfused blood products and primarily acquired infections in areas of malarial endemicity [8]. In our case since the species isolated was Plasmodium falciparum reactivation was ruled out.…”
Section: Discussionmentioning
confidence: 99%